How Not to Argue about the Compatibility of Predictive Processing and 4E Cognition - Yavuz Recep Başoğlu (Institute of Philosophy of the Slovak Academy of Sciences, 2021)
In theories of cognition, 4E approaches to cognition are seen to refrain from employing robust representations in contrast to Predictive Process, where such posits are utilized extensively. Despite this notable dissimilarity with regard to pos-its they employ in explaining certain cognitive phenomena, it has been repeatedly argued that they are in fact compatible. As one may expect, these arguments mostly end up contending either that Predictive Process is actually nonrepresentational or that 4E approaches are representational. In this paper, I will argue that such arguments are inadequate for the indicated purpose for several reasons: the variety of representational posits in Predictive Process, the diverse attitudes of practitioners of 4E approaches toward representations and the unconstrained use of the term “representation” in cognitive science. Hence, here I will try to demonstrate that any single argument, if it depends on representational 4E approaches or nonrepresentational Predictive Process, falls short of encompassing this heterogeneity in pertinent debates. Then, I will analyze similar arguments provided by Jacob Hohwy and Michael Kirchhoff to illustrate how destructive this seemingly ordinary criticism is.